ANALYSIS OF THE IMPACT OF ANCHORING, HERDING BIAS, OVERCONFIDENCE AND ETHICAL CONSIDERATION TOWARDS INVESTMENT DECISION - Robin Robin; Vanne Angelina (Universitas Pakuan, 2020)
There are lots of factors that investors need to take in consideration before investing. Although the importance of external factors is undeniable, in recent decade, experts started to realize the importance of internal factors in investing. This includes behavior and psychological factors. This analysis of internal factor is what we refer to as behavior finance. However, just how important behavior finance is, and how significant it is in investment decision? In this study, researcher aims to determine the impact of anchoring, herding bias, overconfidence, and ethical consideration towards investment decision. Questionnaires were distributed to 149 investors of different backgrounds to determine the impact of behavior finance towards investment decision. PLS-SEM was used to test the research hypotheses. Through this research, it is determined that behavior and psychological biases and tendencies do affect investment decision. It is important to understand behaviors in investing because these behavior biases and tendencies can potentially lead to loss. Understanding behavior finance means investors can avoid behavior biases and rectify mistakes.